Extraction of phosphorus from sewage sludge ash by CO2 blowing method - Toyama, Takeshi (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
Phosphorus is an important element not only for use in fertilizers, but also for the manufacture of industrial products. However, depletion of this resource is a problem. Japan relies on imports for the entire amount of phosphorus it consumes. For this reason, there is an urgent need to secure a stable supply of phosphorus. On the ohter hand, there is waste containg a considerable amount of phosphorus. On of them is sewage sludg ash, but it also contains many heavy metals, extraction of only phosphorus is difficult.
Keywords: Extraction; phosphorus (P)